ANALISA SURAT LUQMAN AYAT 12-19 TERKAIT BIMBINGAN KONSELING ISLAMI DI PONDOK PESANTREN MODERN - Naufal Alifuddin Rahman; Imam Fauji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study analyzes the principles of counseling guidance in the Quran, focusing on Surah Luqman verses 12-19, and examines their implementation at the Darussalam Islamic boarding school. A qualitative approach with a descriptive method was employed, utilizing literature review, documentation, and interviews with BK teachers, caregivers, and students. Observations of students' daily behavior and their relationships with caregivers were also conducted. The research revealed that the counseling guidance at Darussalam Islamic boarding school is based on the Quran, particularly Surah Luqman verses 12-19. The